Changing Pattern of Post-infectious Glomerulonephritis: A Study in South-Western Region of Bangladesh (Medicine Today, 2020)
Introduction: In developing countries like Bangladesh, post-infectious glomerulonephritis (PIGN) is the common form ofacute glomerulonephritis having its changing pattern over recent decades. The aim of the study was to analyze the clinicalprofile of PIGN in local scenario.Materials and Methods: This cross-sectional study was conducted at Shaheed Sheikh AbuNaser Specialized Hospital, Khulna during period from 2017 to 2019. A total of 67 cases of PIGN were identified on thebasis of clinical features, laboratory parameters with recent history of infection. The patients’ records were reviewed withrespect to clinical data. Patients with reduced complement level were included.Result: The age range of the patients wasbetween 2 and 55 years with male predominance. The study revealed that 32.8% of patients had a recent history of sorethroat, 31.3 % of patients had a history of skin infection and rest 35% had a history of fever. Moreover, during presentation68% of patients had hypertension and 37 % of patient had renal impairment. In this study, majority of patients (53%)presented with one plus to two plus proteinuria and the rest of the patients (37%) presented with three plus proteinuria ondipstick. After 2 weeks of follow up, the presence of hematuria found in 58 patients out of 67, proteinuria found in 14patients out of 61 and renal impairment found in 5 patients out of 25.Conclusion: PIGN has been changing with respect toage, proteinuria and renal function. To follow-up periodically and reduction in overcrowding of the patients, would be oneof the superior suggestions to reduce the spread of infectious diseases in our country.Medicine Today 2020 Vol.32(2): 130-133